Rancang Bangun Game Edukasi Siklus Air untuk Media Pembelajaran Siswa Kelas 5 SD - Ariqoh, Reky; Nurkifli, E. Haodudin; Yusup, Dadang Haodudin (Peneliti.net, 2026)
Elementary school students' understanding of the water cycle is often hampered by its abstract nature. This study aims to develop an educational game with a water cycle theme using the Multimedia Development Life Cycle (MDLC) method as an interactive learning medium. The game was developed using GDevelop 5 and tested through alpha testing (by media and material experts) and beta testing (by 5th grade students of SDN 1 Trusmi Kulon). The feasibility test results showed that the game was categorized as very feasible with a feasibility score of 100% from media experts, 80% from material experts, and 93.62% from users. The effectiveness test with N-Gain showed an increase in student understanding with an average score of 56%, which is included in the fairly effective category. These results indicate that the designed educational game effectively supports the science learning process in elementary schools.